2023
DOI: 10.1212/wnl.0000000000207869
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy in Patients With Very Low ASPECTS Scores

Aristeidis H. Katsanos,
Luciana Catanese,
Ashkan Shoamanesh

Abstract: Background and Objectives:Randomized controlled trials (RCTs) have recently established the benefit of endovascular thrombectomy (EVT) in patients with large infarct core on baseline neuroimaging. We evaluated the utility of EVT in patients with very large infarct core, defined as Alberta Stroke Program Early CT scores (ASPECTS) of less than 3.Methods:We performed a systematic review and meta-analysis of the subgroups of patients with baseline ASPECTS scores 0-2 included in RCTs evaluating the utility of EVT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Our findings support the transfer and treatment consideration of patients with large ischemic core stroke presenting to non–EVT-capable centers as well as exploration of opportunities to further optimize clinical outcomes by reducing potential stroke evolution on neuroimaging during transfer through other therapeutic approaches, such as neuroprotection. On the other hand, a 2023 meta-analysis demonstrated that EVT improves outcomes even in patients with very low ASPECTS (0 to 2) . A randomized clinical trial has included patients with ASPECTS of 0 to 2 and their findings, if confirming beneficial effects of EVT in this population, may further support the notion of transferring patients even with very low ASPECTS or longer transfer times for consideration of thrombectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the transfer and treatment consideration of patients with large ischemic core stroke presenting to non–EVT-capable centers as well as exploration of opportunities to further optimize clinical outcomes by reducing potential stroke evolution on neuroimaging during transfer through other therapeutic approaches, such as neuroprotection. On the other hand, a 2023 meta-analysis demonstrated that EVT improves outcomes even in patients with very low ASPECTS (0 to 2) . A randomized clinical trial has included patients with ASPECTS of 0 to 2 and their findings, if confirming beneficial effects of EVT in this population, may further support the notion of transferring patients even with very low ASPECTS or longer transfer times for consideration of thrombectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, our study enrolled patients within 24 hours of witnessed symptoms and the median time of onset to recanalization was approximately 7 hours, which exceeded the inclusion criteria of less than 6.5 hours since last-known-well time in the LASTE trial. 12 A systematic review and meta-analysis 6 found a statistically significant shift in the distribution of mRS scores toward better outcomes in favor of EVT in the pooled analyses of 82 participants enrolled in 2 individual RCTs. However, EVT was not associated with improved 90-day functional outcomes in patients with ASPECTS of 3 or less in the RESCUE-Japan LIMIT trial.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis of subgroups of patients with baseline ASPECTS of 0 to 2 included in the ANGEL-ASPECT trial and SELECT2 trial, a statistically significant shift in the distribution of modified Rankin Scale (mRS) scores toward better outcomes in favor of EVT was observed in the pooled analyses. In the RESCUE-Japan LIMIT trial, EVT was not associated with improved 90-day functional outcomes in patients with ASPECTS of 3 or less.…”
Section: Introductionmentioning
confidence: 99%